An assessment of whether the critical minerals boom and green transition can be leveraged for Zambia's industrialisation and economic development: spotlight on the Copper Mining Sector - Kanyama, Victor Amedzo (School of Economics, 2025)
This study assesses whether Zambia can leverage the critical minerals boom and the global green transition to drive its industrialisation and economic development. As a major copper producer, Zambia holds strategic importance in supplying minerals essential for renewable technologies such as electric vehicles, solar panels, and energy storage systems. However, the country's ability to capitalise on this demand hinges on strengthening productive linkages, integrating into regional and global value chains, and navigating geopolitical competition. The research examines historical policy shifts, the structural barriers that have limited Zambia's economic diversification, and the role of governance and industrial policy in unlocking value addition. The study evaluates Zambia's forward and backward linkages, identifying challenges such as weak local beneficiation, foreign dominance in mining procurement, and policy inconsistencies that constrain industrial growth. Regional collaboration, particularly through Zambia's partnership with the DRC, is explored as a potential avenue for enhancing midstream processing and attracting investment into battery precursor production. Additionally, the geopolitical landscape—marked by competition between the United States, China, and emerging investors—is analysed in relation to Zambia's strategic positioning in the global copper supply chain. Using semi-structured interviews and document analysis, the study outlines actionable policy pathways for Zambia, including industrial strategy refinement, local content enforcement, and institutional reforms. It argues that with coherent policy implementation, infrastructure investment, and a balanced geopolitical approach, Zambia can transition from a raw material exporter to a key player in mineral-based industrialisation, securing long-term economic benefits from the green transition.